The conservation of maize genetic resources native in Tamaulipas - Garza-Castillo, Manuel R. (Universidad Autónoma de Tamaulipas, 2010)
Northeastern Mexico and especially Tamaulipas has played an important role in the domestication process and as a source of genetic resources of maize. However, it is increasingly evident the effect of genetic erosion in these materials. In the State, the Universidad Autónoma de Tamaulipas from the eighties, started some work for the conservation of native maize genetic resources, ex situ in the form with the creation of a small seed bank, with the support of Consejo Nacional de Ciencia y Tecnología, the Secretaría de Educación Pública, the Sistema Nacional of Recursos Fitogenéticos, the Comisión Nacional para la Conservación and the Uso de la Biodiversidad y the Comisión Nacional de Áreas Naturales Protegidas; all of whom have supported to give continuity to these conservation schemes. This article proposes a broader and more holistic type for the use and management of the potential of landraces of maize in Tamaulipas.